Respiratory treatment and prevention - Pokorski, Mieczyslaw (Springer, 2016)
The goal of this book is to further insight into the challenges related to respiratory health. Medical experts present their lines of scientific investigations on how to contain the disease, care for patients, and use preventive measures, with a focus on pulmonary-related disorders. Progress in the diagnostics and treatment of major infectious diseases affecting humanity such as tuberculosis, malaria, fungal and viral contagions is tackled. Other chapters provide some background information on the mechanisms and prevention of non-communicable diseases. New aspects of the etiology of sarcoidosis, air pollution-related lung cancer, and sleep disordered breathing are presented. Preventive measures of health in general and respiratory health in particular cannot do without a reminder of cigarette smoke avoidance and the respiratory aftermath of the smoking habit. The book presents scientific evidence-based practice knowledge. It is intended for healthcare professionals, specifically pulmonary specialists, primary care physicians, and all scientifically-minded individuals involved in the care of patients.- Resumé vydavatel
Includes index.
Keywords: nemoci dýchacího ústrojí; nemoci plic; respiratory tract diseases; pulmonary diseases; elektronické knihy; sborníky; electronic books; papers of several authors